Antimicrobial resistance of aerobes and facultative anaerobes isolated from the oral cavity - Gaetti-Jardim, Ellen Cristina [UNESP]; Marqueti, Antônio Carlos [UNESP]; Faverani, Leonardo Perez [UNESP]; Jardim Júnior, Elerson Gaetti [UNESP] (FapUNIFESP (SciELO), 2010)
Objectives: This study evaluated the resistance to antimicrobials of aerobes and facultative anaerobes isolated from patients wearing complete dentures, patients with gingivitis and periodontitis, and periodontally health subjects. Material and Methods: Three hundred and four isolates were tested. The minimal inhibitory concentrations of the drugs were evaluated through the agar dilution method using Mueller-Hinton agar. Results: The most active antimicrobial drugs were the carbapenems (meropenem and imipenem), and resistance to these drugs was restrict to 1.6-2.3% of the isolates, as well as ciprofloxacin and rifampin. Microbial resistance to ampicillin, amoxicillin/clavulanic acid, cefoxitin, cephalothin, amikacin, chloramphenicol and nalidixic acid was particularly high. In most cases, the resistance to β-lactams was mediated by the production of hydrolytic enzymes, especially in gram-negative enteric rods, while enterococci did not evidence production of these enzymes. The association amoxicillin/clavulanic acid was not effective in 28.3% of the tested isolates. Conclusions: The results of this investigation confirmed that the oral cavity of patients with periodontitis and gingivitis, and particularly edentulous patients wearing complete dentures could harbor microorganisms with several antimicrobial resistance markers, and these microorganisms are frequently implicated in multiresistant, systemic, oral or nosocomial infections.
Keywords: Anti-bacterial agents; Bacteria; Gingivitis; Periodontitis